Comparative study evaluating the efficacy of topical azithromycin versus oral doxycycline in the treatment of meibomian gland dysfunction - Ahmad, Adnan; Rehman, Mubashir (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the efficacy of topical azithromycin drops versus oral doxycycline therapy in meibomian gland dysfunction. Method: The prospective randomised trial was conducted from December 2019 to June 2020 at the Qazi Hussain Ahmad Medical Complex, Nowshera, Pakistan, and comprised patients of either gender aged 26-42 years having long-standing posterior blepharitis / meibomian gland dysfunction. The subjects were randomised into two equal groups. Both the groups were advised to do warm compresses and lid massage three times a day for 5min each for 4 weeks. In addition, group A group received azithromycin 1% drops 2 times/day for 1 week, followed by once a day for 3 weeks, while group B received oral doxycycline 100mg once a day for 4 weeks. Baseline, midstream at 2 weeks and post-intervention status, including subjective symptoms, were compared. Results: Of the 60 subjects enrolled, there were 30(50%) in each of the two groups; 32(53.3%) males and 28(46.4%) females. While all 30(100%) the participants in group A completed the trial without any adverse reaction to medication, 8(26.7%) in group B quit midstream owing to anorexia/nausea and gastrointestinal discomfort. Compared to baseline, reduction in both subjective and objective features of the disease in both groups was noted regardless of gender (p=0.08). No significant difference was evident in symptoms healing rate and improvement in foreign body sensation between the groups (p>0.05). Group A improved eye redness, while group B proved better in respect of meibomian glands obstruction healing and corneal staining p<0.05). Conclusion: Both topical azithromycin and oral doxycycline were effective and had their own edge as far as symptomatic improvement was concerned in the treatment of meibomian gland dysfunction. Key Words: Meibomian gland dysfunction, Topical azithromycin, Oral doxycycline, Efficacy.